2020
DOI: 10.32794/mr11250053
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin in yeast and fermented beverages: analytical tools for detection, physiological role and biosynthesis

Abstract: The recently established relation between the metabolism of aromatic amino acids of yeast and the production of different bioactive molecules during fermentation opens up new and interesting research topics. Among these molecules, melatonin has drawn researchers’ attention in the last decade given its potential benefits for human health. This review summarizes melatonin production in fermented beverages, and conventional and current methods for detecting melatonin in yeast-derived samples. In addition, the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 78 publications
2
2
0
Order By: Relevance
“…A similar observation has been made by Muñiz‐Calvo et al. (2020), pointing out the importance of extraction approach for proper sample preparation and precise acquisition of the results. As the extraction approach considerably impact the accuracy and reliability of MEL and MI determination in tested materials, including fermented material (matrix effect), the use of sufficient extraction technique such as solid liquid‐phase extraction and solid‐phase extraction (SPE) is strongly recommended prior to chromatographic analysis.…”
Section: Biosynthesis Of Melatonin Under Fermentation Conditionssupporting
confidence: 82%
See 2 more Smart Citations
“…A similar observation has been made by Muñiz‐Calvo et al. (2020), pointing out the importance of extraction approach for proper sample preparation and precise acquisition of the results. As the extraction approach considerably impact the accuracy and reliability of MEL and MI determination in tested materials, including fermented material (matrix effect), the use of sufficient extraction technique such as solid liquid‐phase extraction and solid‐phase extraction (SPE) is strongly recommended prior to chromatographic analysis.…”
Section: Biosynthesis Of Melatonin Under Fermentation Conditionssupporting
confidence: 82%
“…The authors concluded that during the lag phase period, MEL was bound to six proteins with molecular weights from 55 to 35 kDa; hence, proper separation technologies are those that can ensure sufficient MEL extraction from various proteins during the lag phase. A similar observation has been made by Muñiz-Calvo et al (2020), pointing out the importance of extraction approach for proper sample preparation and precise acquisition of the results. As the extraction approach considerably impact the accuracy and reliability of MEL and MI determination in tested materials, including fermented material (matrix effect), the use of sufficient extraction technique such as solid liquid-phase extraction and solid-phase extraction (SPE) is strongly recommended prior to chromatographic analysis.…”
Section: Biosynthesis Of Melatonin Under Fermentation Conditionssupporting
confidence: 78%
See 1 more Smart Citation
“…In microorganisms, there are few studies on the melatonin biosynthesis pathway [ 82 ]. Saccharomyces and bacteria ( Geobacillus , Bacillus , and Pseudomonas ) produced both serotonin and melatonin at different concentrations [ 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. Moreover, the production of melatonin was evidenced by other authors in the cultures of the yeasts Pichia kluyveri , Saccharomyces cerevisiae , and S. uvarum and bacteria ( Agrobacterium , Pseudomonas , Variovorax , Bacillus , and Oenococcus ) [ 85 , 90 , 91 ] and previously in the photosynthetic bacteria Rhodospirillum rubrum [ 92 ] and Erythrobacter longus [ 93 ] and Escherichia coli [ 94 ].…”
Section: Biosynthesis Of Melatoninmentioning
confidence: 99%